Common offences made by companies under registration of Businesses Act 1956 and Companies Act 1965; that can be compounds by SSM / Mazliza Zainal Abidin - Zainal Abidin, Mazliza (Faculty of Business and Management, 2010)
This project paper studies on the common offences made by companies that can be compound by Syarikat Suruhanjaya Malaysia (SSM). These offences are made under Registration of Businesses Act 1956 and Companies Act 1965. The aim is to encourage companies and firms to register with SSM and to make them realized the common offences they should avoid. By studying this case, I clarify the processes and procedures that are applied by SSM in managing the issuance of compound under both acts. Besides, the studies include some of common offences under Registration of Businesses Act 1956 and Companies Act 1965, and the amount that can be compound. Data have been collected from archives, online newspapers, SSM Bulletin, annual reports and published reports. These studies also shows that internal and external errors such as loose monitoring actions, poor rapport between director and company secretary, lack of knowledge in handling business, and do not have awareness do exist in business. Thus, the weaknesses must be improved to make sure that directors and owner of the business do not make the same offences.